2020
DOI: 10.1051/0004-6361/202038367
|View full text |Cite
|
Sign up to set email alerts
|

AQUA: a collection of H2O equations of state for planetary models

Abstract: Context. Water is one of the key chemical elements in planetary structure modelling. Due to its complex phase diagram, equations of state often only cover parts of the pressure-temperature space needed in planetary modelling. Aims. We aim to construct an equation of state of H2O spanning a very wide range, from 0.1 Pa to 400 TPa and 150 to 105 K, which can be used to model the interior of planets. Methods. We combined equations of state valid in localised regions to form a continuous equation of state spanning… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…For the forward model, we assume that each planet is composed of four layers: an iron-sulfur inner core, a mantle, a water layer, and a gas layer. We used the equation of state (EOS) for Hakim et al (2018) for the core, the EOS from Sotin et al (2007) for the silicate mantle, and the EOS from Haldemann et al (2020) for the water. These three layers constitute the 'solid' part of the planets.…”
Section: Internal Structure Modellingmentioning
confidence: 99%
“…For the forward model, we assume that each planet is composed of four layers: an iron-sulfur inner core, a mantle, a water layer, and a gas layer. We used the equation of state (EOS) for Hakim et al (2018) for the core, the EOS from Sotin et al (2007) for the silicate mantle, and the EOS from Haldemann et al (2020) for the water. These three layers constitute the 'solid' part of the planets.…”
Section: Internal Structure Modellingmentioning
confidence: 99%
“…The problem with associating the second peak with water-rich planets is that it cannot explain why such planets do not fill the valley. Cores containing 50% rock-50% ice by mass would fall in the radius valley if they had a mass of ∼3-6 M ⊕ (Sotin et al 2007;Zeng et al 2019;Haldemann et al 2020;Owen & Wu 2017;Gupta & Schlichting 2019). Zeng et al (2019) showed that the Kepler size distribution can be matched if the icy planets are assumed to follow the mass distribution suggested by RV measurements, which encompasses masses in the range ∼6-15 M ⊕ , with a peak at ∼9 M ⊕ .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the position of the water line in the diagram is very sensitive to used EOS (e.g. Haldemann et al 2020). Fig.…”
Section: Parametermentioning
confidence: 99%